Development and application of a method for analysis of lufenuron in wheat flour by gas chromatography-mass spectrometry and confirmation of bio-efficacy against Tribolium castaneum (Herbst) (Coleoptera : Tenebrionidae) - Ahire, Kedar C.; Arora, Manjit S.; Mukherjee, Samindra N. (Journal of Chromatography B-Analytical Technologies in the Biomedical and Life Sciences, 2008)
A new analytical method using gas chromatography with mass spectrometry (GC-MS) for the quantitative determination of lufenuron, a benzoylphenylurea (BPU) class of insecticide, from wheat flour has been developed and applied for time-dependant residue monitoring in treated wheat flour. The analyte was extracted from wheat flour by a single step solid-liquid extraction by using ethyl acetate and subsequently cleaned up using the Primary Secondary Amine as a sorbent prior to GC-MS analysis. The present method provides sufficient sensitivity as reflected by the values of limit of detection (LOD) and limit of quantification (LOQ), 5 ng/mL (S/N similar to 3) and 50 ng/mL (the lowest validation point on the calibration curve), respectively. The calibration curve showed an excellent linearity in the concentration range of 50-1000 ng/mL (r(2) = 0.998). The average recovery for spiked samples at three concentrations (150, 300, and 450 ng/g) was 98.23 +/- 2.52% R.S.D. The method was applied for the determination of lufenuron residues in treated wheat flour samples. Simultaneous determination of bio-efficacy of lufenuron residues was also carried out against the red flour beetle, Tribolium castaneum to correlate the actual residual effect of lufenuron as detected by the analytical method, over a period of 3 months. The findings revealed that the residual concentration of lufenuron were neither uniform nor in descending order over a period of 3 months in wheat flour, possibly because of an uneven dispersal in the treated wheat which was subsequently milled into flour, as confirmed by GC-MS analysis. However, the residues of lufenuron were sufficient to produce 100% mortality of T. castaneum larvae up to 3 months. The results have been discussed in view of the potential of lufenuron as a candidate molecule for the control of stored product pests. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: bio-efficacy; GC-MS; lufenuron; method development; residue analysis; Tribolium castaneum; Wheat